2004
DOI: 10.1590/s1415-790x2004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação higiênico-sanitária e físico-estrutural dos supermercados de uma cidade do Sudeste do Brasil

Abstract: Embora os supermercados sejam o principal local de venda de alimentos no Brasil, são pouco estudados em relação aos aspectos sanitários. Em Ribeirão Preto, representam o principal local de venda de alimentos para todas as classes sociais, ao mesmo tempo que vêm sendo causa de número crescente do total de reclamações feitas à Divisão de Vigilância Sanitária (Visa) do município. Esta investigação, conduzida durante as inspeções de rotina da Divisão de Vigilância Sanitária, avaliou as condições higiênico-sanitári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
0
9
0
12
Order By: Relevance
“…Eventually, personnel not wearing uniform and/or cap accessed the production area, and the facility had no rules for external visitors. According to Oliveira, Rolim, Moura, and Mota (2008b), 30.7% of food manipulators working in butcher shops in the city of Belém, Brazil, have never participated in any kind of training about Best Management Practices, being a similar situation reported by Valente and Passos (2004) for food handlers in supermarkets.…”
Section: Food Manipulator Employeesmentioning
confidence: 86%
See 2 more Smart Citations
“…Eventually, personnel not wearing uniform and/or cap accessed the production area, and the facility had no rules for external visitors. According to Oliveira, Rolim, Moura, and Mota (2008b), 30.7% of food manipulators working in butcher shops in the city of Belém, Brazil, have never participated in any kind of training about Best Management Practices, being a similar situation reported by Valente and Passos (2004) for food handlers in supermarkets.…”
Section: Food Manipulator Employeesmentioning
confidence: 86%
“…Valente and Passos (2004) reported that structural problems in bathrooms and locker rooms may compromise employee hygiene, thus contributing for meat contamination, jas.ccsenet.org Journal of Agricultural Science Vol. 10, No.…”
Section: Facility Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…The data were collected from April to July 2011 using a checklist of good practices containing questions based on Similar data were found by Valente and Passos (2004) using inspection certificates in 46 supermarkets in southeastern Brazil. They found that 79.3% of those establishments were considered deficient (Group 3), 19.0% fell into Group 2 category, and only 1.7% fell into Group 1 category.…”
Section: Methodsmentioning
confidence: 99%
“…Vale ressaltar o papel da Vigilância Sanitária não apenas na fiscalização, mas também na sua atuação como multiplicador das boas práticas higiênico-sanitárias mediante atividades educativas permanentes dirigidas aos consumidores, alertando para os riscos representados pela manipulação inadequada (VALENTE, 2004). As boas práticas de fabricação formam um dos componentes fundamentais para a segurança alimentar, pois onde se tem o risco de perigos, estes devem ser controlados, garantindo a sua integridade e eficácia e, adquirindo assim a segurança alimentar.…”
Section: Vigilancia Sanitaria Introduçãounclassified